2014
DOI: 10.1590/s1679-45082014ao2881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different intensities of physical exercise on insulin sensitivity and protein kinase B/Akt activity in skeletal muscle of obese mice

Abstract: Objective:To investigate the effects of different intensities of acute exercise on insulin sensitivity and protein kinase B/Akt activity in skeletal muscle of obese mice.Methods:Swiss mice were randomly divided into four groups, and fed either a standard diet (control group) or high fat diet (obese sedentary group and obese exercise group 1 and 2) for 12 weeks. Two different exercise protocols were used: swimming for 1 hour with or without an overload of 5% body weight. The insulin tolerance test was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Studies investigating the effects of aerobic training on modulation of pro-inflammatory molecules, such as JNK, TNF-α, IKK and others, and on improvement of insulin sensitivity have been published. ( 11 - 17 ) Investigations in rats with fat-rich diet-induced obesity revealed that aerobic exercise reduces molecules in the pro-inflammatory pathway, and increases intracellular insulin signaling, leading to increased sensitivity to this hormone. ( 13 , 14 , 16 ) However, further studies investigating the effects of different types of physical exercise on inflammatory markers associated with insulin resistance are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the effects of aerobic training on modulation of pro-inflammatory molecules, such as JNK, TNF-α, IKK and others, and on improvement of insulin sensitivity have been published. ( 11 - 17 ) Investigations in rats with fat-rich diet-induced obesity revealed that aerobic exercise reduces molecules in the pro-inflammatory pathway, and increases intracellular insulin signaling, leading to increased sensitivity to this hormone. ( 13 , 14 , 16 ) However, further studies investigating the effects of different types of physical exercise on inflammatory markers associated with insulin resistance are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the exercise therapy is useful in enhancing the physical strength and preventing complications, which are known to be effective in diabetes treatment [ 9 ]. Regular exercise reduces the glucose concentrations in the blood [ 10 ], increases the insulin sensitivity of the peripheral tissue including the muscles [ 11 ], and also helps to control the weight of obese diabetic patients [ 12 ]. Aerobic exercises are generally practiced by diabetic patients until now, but the elderly patients with diabetes have difficulty in performing exercises; this is because they have problems of diabetic complications or retrogression in functional capabilities due to obesity, degenerative arthritis, cardiovascular disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technique has shown similar beneficial effects on obesity and hepatic steatosis in mouse models . The effect of exercise has mostly been investigated in the working skeletal muscle, where it has been shown to induce the transcription of genes involved in glucose and fatty acid metabolism and myogenesis . The liver plays a central role in glucose and lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…11 The effect of exercise has mostly been investigated in the working skeletal muscle, where it has been shown to induce the transcription of genes involved in glucose and fatty acid metabolism and myogenesis. [12][13][14] The liver plays a central role in glucose and lipid homeostasis. Activities of gluconeogenic and lipogenic enzymes have been reported to increase and decrease, respectively, in response to physical activity.…”
Section: Introductionmentioning
confidence: 99%